Penerapan Manajemen Lingkungan ISO 14001 dalam Mitigasi Tumpahan Minyak dari Kerusakan Infrastruktur di PT. KPI RU II Dumai - Azzura, Nasla Siva; Siska, Syafni Yelvi (Jurnal Cakrawala Bahari, 2025)
The structural damage to port infrastructure at PT Kilang Pertamina Internasional (KPI) RU II Dumai poses a significant risk of oil spills, which may impact marine ecosystems, company operations, and corporate reputation. The implementation of the ISO 14001 Environmental Management System serves as a critical instrument in preventing, mitigating, and recovering from such environmental incidents. This study aims to analyze the application of ISO 14001 in mitigating oil spill risks caused by infrastructure failures, focusing on planning, emergency response procedures, monitoring, and continuous evaluation. The research adopts a qualitative approach through literature review, field observation, and interviews with relevant stakeholders. The findings indicate that the adoption of ISO 14001 enhances corporate preparedness by identifying environmental aspects and impacts, developing Standard Operating Procedures (SOP) for oil spill response, and strengthening human resource competencies. Furthermore, the environmental management system supports regulatory compliance, minimizes economic losses, and fosters an environmentally conscious culture within refinery operations. In conclusion, the implementation of ISO 14001 is not only a matter of compliance but also an effective strategy for ensuring operational sustainability and environmental protection at PT KPI RU II Dumai.